A nonlinear FE analysis to model progressive fatigue damage of cross-ply laminates under pin-loaded conditions. (February 2019) - Samareh-Mousavi, Seyed Sina; Mandegarian, Sepanta; Taheri-Behrooz, Fathollah
Highlights: A nonlinear progressive fatigue damage model for cross-ply laminates. A user-defined material subroutine to implement nonlinear fatigue model in ABAQUS. Fatigue life simulation of pin-loaded cross ply composite laminates. Abstract: Involving several damages and failure mechanisms result in a rather complex fatigue process of composite materials. Inhomogeneity, anisotropy and nonlinear nature of composite materials require advanced nonlinear modeling techniques of strength and fatigue. In this paper, a progressive fatigue damage model is proposed by considering the nonlinearity effects of in-plane shear stress/strain relationship. To this aim, fatigue failure criteria and material property degradations rules are derived based on material nonlinearity. The mathematical model is applied through a UMAT subroutine code developed in ABAQUS commercial software. To validate the model, life predictions are compared with the available experimental results of coupon specimen and pin-loaded carbon/epoxy cross-ply laminates. The presented finite element nonlinear progressive fatigue damage model improved the life prediction for both geometries. For coupon specimen and pin-loaded simulations, the present model reduced the average error of life predictions by 80% and 50%, respectively compared to the conventional linear models. From results of the pin-loaded model, the nonlinear assumption predicts a shorter life at high external loads due to higher stress in the fiber direction of on-axis plies as critical elements of the laminate; however, at lower external loads, both linear and nonlinear models predict similar stress state and life.